Intercropping Options for Higher Profitability in sub-tropical sugarcane farming - Singh, A K; Pathak, A D; Singh, Ekta (Indian Farming, 2017)
The area under sugarcane during 2015-16 has soared up to 4.92 million hectares and produced 341.4 million tonnes of cane with an average productivity of 69.4 tonnes/hectare. In view of dwindling land resources, changing market scenario, consumers’ preferences and global competitions, new income generating opportunities need to be created through intercropping in sugarcane.